2022
DOI: 10.3390/ijerph191710789
|View full text |Cite
|
Sign up to set email alerts
|

Falls at the Geriatric Hospital Ward in the Context of Risk Factors of Falling Detected in a Comprehensive Geriatric Assessment

Abstract: It is only by knowing the most common causes of falls in the hospital that appropriate and targeted fall prevention measures can be implemented. This study aimed to assess the frequency of falls in a hospital geriatrics ward and the circumstances in which they occurred and evaluate the parameters of the comprehensive geriatric assessment (CGA) correlating with falls. We considered medical, functional, and nutritional factors associated with falls and built multivariable logistic regression analysis models. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 42 publications
0
22
0
1
Order By: Relevance
“…As quedas são frequentes em pessoas idosas e tem repercussões sociais e econômicas para os pacientes e suas famílias, visto que podem causar incapacidade, restrição das atividades de vida diária, medo de novas quedas, reduzindo a qualidade de vida e independência desses pacientes (12). De acordo com um estudo polonês, quais 45% dos indivíduos com idade superior há 75 anos relataram pelo menos uma queda no período de 1 ano (18), achado corroborado no presente estudo.…”
Section: Discussionunclassified
“…As quedas são frequentes em pessoas idosas e tem repercussões sociais e econômicas para os pacientes e suas famílias, visto que podem causar incapacidade, restrição das atividades de vida diária, medo de novas quedas, reduzindo a qualidade de vida e independência desses pacientes (12). De acordo com um estudo polonês, quais 45% dos indivíduos com idade superior há 75 anos relataram pelo menos uma queda no período de 1 ano (18), achado corroborado no presente estudo.…”
Section: Discussionunclassified
“…The above assessment contents are the most direct clinical reflection of the older patient's comprehensive health, which are also mostly concerned by clinical workers. Relevant studies confirmed that CGA showed good results in fall screening and benefits in making comprehensive intervention plan according to prevent falls in the hospital 10,11 . Thus, CGA is an effective method from multiple perspectives in fall screening 12 …”
Section: Introductionmentioning
confidence: 89%
“…Relevant studies confirmed that CGA showed good results in fall screening and benefits in making comprehensive intervention plan according to prevent falls in the hospital. 10,11 Thus, CGA is an effective method from multiple perspectives in fall screening. 12 The goal of the present study was to evaluate the fall status of elderly patients in outpatient and inpatient departments of geriatrics by CGA and to analyze its related factors.…”
Section: Comprehensive Geriatric Assessment (Cga) Initially Introduce...mentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors of falls, according to the simplest classification, can be divided into intrinsic and extrinsic [ 8 ]. The first group includes nonmodifiable factors, such as age and gender and health-related factors, while the other group includes environmental factors such as home surroundings, government policy on environmental design, housing standards, public transport, neighborhood conditions, and social networks [ 9 ]. In the elderly population, an accumulation of risk factors can be observed in both groups.…”
Section: Introductionmentioning
confidence: 99%